The Relationship between Nomophobia and Learning Motivation Muslim Students in Java - Monalisa; Livna Alfiyanah; Silvia Melani Putri; Yogi Damai Syaputra; Mandalia, Siska (Pamomong: Journal of Islamic Educational Counseling, 2024)
This research aims to assess the level of nomophobia among students and their learning motivation and explore the relationship between these two factors. Utilizing a quantitative methodology with a correlational approach, the study sampled 356 students from across the island of Java through convenience sampling techniques. Data was collected via a nomophobia questionnaire (NMP-Q), which consists of 16 items with a reliability score of .899, and a learning motivation scale with 13 items and a reliability score of .847, distributed through WhatsApp. The data analysis involved quantitative descriptive analysis and Pearson product-moment correlation analysis. The findings reveal that students exhibit a high level of nomophobia while their learning motivation is low. Additionally, there is a significant inverse relationship between nomophobia and learning motivation, indicating that higher levels of nomophobia are associated with lower motivation to learn. Conversely, lower levels of nomophobia correlate with increased learning motivation. These research findings can serve as a foundation for counselors to develop appropriate interventions to address nomophobia and enhance students' motivation to learn.